2019
DOI: 10.1186/s12955-019-1079-z
|View full text |Cite
|
Sign up to set email alerts
|

Translation, transcultural adaptation, reliability and validation of the pelvic organ prolapse quality of life (P-QoL) in Amharic

Abstract: BackgroundThe Prolapse Quality of Life (P-QoL) is a disease-specific instrument designed to measure the health-related quality of life in women with prolapse; however, there is no Amharic version of the instrument. The aim of this study were to translate the P-QoL into Amharic and evaluate its psychometric properties among adult women.MethodsWe followed an intercultural adaptation procedure to translate and adapt the P-QoL. A forward–backward translation, face validity interviews with experts and cognitive deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
(108 reference statements)
1
14
0
1
Order By: Relevance
“…The P-QoL is a PRO tool that can measure the impact of surgical interventions on patient's HRQoL. This study uses locally validated P-QoL to demonstrate an improvement in patient-reported HRQoL after native tissue repair of prolapse in Ethiopia [19]. Thus, our study adds to the evidence that P-QoL can be used as a PRO tool to demonstrate patient impact after surgery in LMIC, speci cally in Ethiopia.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The P-QoL is a PRO tool that can measure the impact of surgical interventions on patient's HRQoL. This study uses locally validated P-QoL to demonstrate an improvement in patient-reported HRQoL after native tissue repair of prolapse in Ethiopia [19]. Thus, our study adds to the evidence that P-QoL can be used as a PRO tool to demonstrate patient impact after surgery in LMIC, speci cally in Ethiopia.…”
Section: Discussionmentioning
confidence: 89%
“…A higher score indicates poor QoL in each domain [13]. This study used a validated Amharic version of P-QoL [19]. The Amharic version had three components: physical (PC; including GHP, PI, PL, RL SL, and SM), psychological (PSC; including EMO and SE), and personal relationship (PRC; containing PR) [19].…”
Section: Evaluation Of Hrqolmentioning
confidence: 99%
“…But many are di cult to administer and may be di cult for populations with high illiteracy rates to understand [1]. However, P-QoL is simple and quick to use tool approximately taking 30 min to administer using face-to-face [26]. Our study adds to the evidence that P-QoL can be used as a PRO tool to demonstrate patient impact after surgery in LMIC, speci cally Ethiopia.…”
Section: Discussionmentioning
confidence: 89%
“…The Amharic version had three components: physical (PC; including GHP, PI, PL, RL SL, and SM), psychological (PSC; including EMO and SE), and social/personal relationship component (PRC; containing PR). The Amharic version is easy to use, can be administered face-to-face and is publicly available [26]. This study measured QoL using domains for PC, PSC, and PRC of the P-QoL instrument.…”
Section: Study Instrumentsmentioning
confidence: 99%
“…The P-QoL is a PRO tool that can measure the impact of surgical interventions on patient’s HRQoL. This study uses locally validated P-QoL to demonstrate an improvement in patient-reported HRQoL after native tissue repair of prolapse in Ethiopia [ 19 ]. Thus, our study adds to the evidence that P-QoL can be used as a PRO tool to demonstrate patient impact after surgery in LMIC, specifically in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%